System of Setting Traditional Settlement in Sentani Lake Papua Island Based on Cultural Defense - Deasy Widyastomo; Ainun Nurin Sharvina (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
System of setting is a system of physical and spatial elements that used for some activities. This system depends on culture. Traditional settlement is a form of cultural embodiment. Traditional settlement in Sentani Lake Papua Island has a spatial system that located on the shore of Lake Sentani. The settlement form is inluenfed by culture. This study aims to elaborate settlement form and cultural defense and security of the community. The method used in this research is intrinsic case study by descriptive qualitative analysis. Case study are the oldest Sentani indigenous village based on historical references in 1907, and the current traditional village. The results of the study found that traditional Sentani settlements consist of two form. The first form is caused by the effect of security due to the intervention of outside tribes, the second form was caused by his closeness to God.
Keywords: System of setting; settlement patterns; Sentani lake Papua Island; cultural defense